Pemanfaatan Video Animasi untuk Meningkatkan Kesiapsiagaan Bencana pada Ibu Hamil, Nifas dan Menyusui di Kecamatan Padang Utara Kota Padang - Lita Angelina Saputri; Farida BD; Yussie Ater Merry (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Natural disaster often cause health problems in pregnancy, postpartum and breastfeeding. When a disaster occurs, pregnant women, babies and children are vulnerable groups. The aim of this community service is to increase the knowledge about disaster preparedness using animated videos The location of this community service activity is North Padang District which focused in Ulak Karang Selatan District. The activity occured in August 2023 with 45 respondents. In this activity, material is provided via Power Point and presenting animated videos to provide education to pregnant, postpartum, breastfeeding mothers and health cadres. Pretest and post test questioners were used in evaluation. It was found that respondents knowledge about disasters increased to 100%, the negative impact of disasters became 97%, preparation for disasters by pregnant women was 95%, preparing an emergency kit was 97%, which must be 90% are carried out when a tornado occurs, 95% are carried out in evacuation centers and 90% of possible complications are carried out. It is hoped that future community service activities will involve the presence of more people. So that this service activity can be carried out continuously.